Response of wild bee diversity, abundance, and functional traits to vineyard inter‐row management intensity and landscape diversity across Europe. Issue 7 (12th March 2019) - Kratschmer, Sophie; Pachinger, Bärbel; Schwantzer, Martina; Paredes, Daniel; Guzmán, Gema; Goméz, José A.; Entrenas, José A.; Guernion, Muriel; Burel, Françoise; Nicolai, Annegret; Fertil, Albin; Popescu, Daniela; et al.
Abstract: Agricultural intensification is a major driver of wild bee decline. Vineyards may be inhabited by plant and animal species, especially when the inter‐row space is vegetated with spontaneous vegetation or cover crops. Wild bees depend on floral resources and suitable nesting sites which may be found in vineyard inter‐rows or in viticultural landscapes. Inter‐row vegetation is managed by mulching, tillage, and/or herbicide application and results in habitat degradation when applied intensively. Here, we hypothesize that lower vegetation management intensities, higher floral resources, and landscape diversity affect wild bee diversity and abundance dependent on their functional traits. We sampled wild bees semi‐quantitatively in 63 vineyards representing different vegetation management intensities across Europe in 2016. A proxy for floral resource availability was based on visual flower cover estimations. Management intensity was assessed by vegetation cover (%) twice a year per vineyard. The Shannon Landscape Diversity Index was used as a proxy for landscape diversity within a 750 m radius around each vineyard center point. Wild bee communities were clustered by country. At the country level, between 20 and 64 wild bee species were identified. Increased floral resource availability and extensive vegetation management both affected wild bee diversity and abundance in vineyards strongly positively. Increased landscape diversity had a small positive effect on wild bee diversity but compensated for the negative effect of low floral resource availability by increasing eusocial bee abundance. We conclude that wild bee diversity and abundance in vineyards is efficiently promoted by increasing floral resources and reducing vegetation management frequency. High landscape diversity further compensates for low floral resources in vineyards and increases pollinating insect abundance in viticulture landscapes. Abstract : Wild bee diversity, abundance, and functional traits in European vineyards are positively affected by high floral resources and extensive management intensities in vineyard inter‐rows. The landscape diversity has a smaller positive effect on wild bees in vineyard inter‐rows compared to management and floral resources. However, the negative effect of low floral resources for eusocial wild bees is compensated by increased landscape diversity.